Risk Factors of Lymphedema in a Prospective Breast Cancer Survivorship Study: The Pathways Study - Kwan, Marilyn L. (2010)
OBJECTIVE: To determine the incidence of breast cancer-related lymphedema (BCRL) during the early survivorship period, and demographic, lifestyle, and clinical factors associated with BCRL development. DESIGN: The Pathways Study, a prospective cohort study of breast cancer survivors with a mean follow-up of 20.9 months. SETTING: Kaiser Permanente Northern California (KPNC) Medical Care Program. PARTICIPANTS: 997 women diagnosed from January 2006 to October 2007 with primary invasive breast cancer and at least 21 years of age at diagnosis, had no prior history of any cancer, and spoke English, Spanish, or Chinese. MAIN OUTCOME MEASURES: Clinical indication of BCRL as determined from outpatient or hospitalization diagnostic codes, outpatient procedural codes, and durable medical equipment orders. RESULTS: 133 women (13.3%) had a clinical indication of BCRL, with a mean time to diagnosis of 8.3 months (range: 0.7–27.3). Being African American (HR = 1.93; 95% CI: 1.00–3.72) or more educated (p trend = 0.03) was associated with an increased risk of BCRL. Removal of at least one lymph node (HR = 1.04; 95% CI: 1.02–1.07) was associated with increased risk, yet no significant association was observed for type of lymph node surgery. Being obese at breast cancer diagnosis was suggestive of an elevated risk (HR = 1.43; 95% CI: 0.88–2.31). CONCLUSIONS: In a large cohort study, BCRL occurs among a substantial proportion of early breast cancer survivors. Our findings agree with previous studies on the increased risk of BCRL with removal of lymph nodes and being obese, yet point to differential risk by race/ethnicity.